TAMARINDUS INDICA L. (FABACEAE): EXTENT OF EXPLORED USE IN TRADITIONAL MEDICINE - VUYYALA, BALAKRISHNA; KUMAR, D SENTHIL; LAKSHMI, THAKKALAPALLY (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Tamarind (Tamarindus indica L.) belongs to the family of Fabaceae (Leguminosae), subfamily Caesalpinioideae, is a very important food within the tropics. Medicinal plants are the rear bone of traditional medicine (TM). TM is vital in tropical countries: Contrary to pharmaceuticals, pharmacological, and pharmacotherapy. T. indica is employed as TM in India, Africa, Pakistan, Bangladesh, Nigeria, and most of the tropical countries. It is used traditionally in abdominal pain, diarrhea and dysentery, helminths infections, wound healing, malaria and fever, constipation, inflammation, cell cytotoxicity, gonorrhea, and eye diseases. It is numerous chemical values and is rich in phytochemicals, and hence, the plant is reported to possess antidiabetic activity, antimicrobial activity, antivenomic activity, antioxidant activity, antimalarial activity, hepatoprotective activity, antiasthmatic activity, laxative activity, and antihyperlipidemic activity. Thus, the aim of the present review demonstrates the plant contains in leaves, seeds, roots, pulp, fruits, and flowers an excellent sort of bioactive substances that have beneficial effects on human health and therefore the possibility of application in various tropical, pharmaceutical, and industrial sectors.